Dietary Alpha-Lipoic Acid Alleviated Hepatic Glycogen Deposition and Improved Inflammation Response of Largemouth Bass (Micropterus salmoides) Fed on High Dietary Carbohydrates - Zishuo Fang; Xianwei Pan; Ye Gong; Nihe Zhang; Shiwen Chen; Ning Liu; Naisong Chen; Songlin Li (Fishes)
In order to mitigate the adverse effects of high carbohydrates on largemouth bass and to investigate the feasibility of LA as a feed additive, the present study observed the effects of added α-lipoic acid (LA) on growth performance, glucose metabolism and immunity in largemouth bass fed on high dietary carbohydrates (10% α-cassava starch inclusion). A total of 315 juvenile largemouth bass (initial body weight, 5.09 ± 0.10 g) were divided into nine tanks (800 L) (upper radius 0.65 m × lower radius 0.5 m × height 1 m), with each holding 35 fish. Three iso-nitrogenous and iso-lipidic diets supplementing with 0 g/kg, 0.5 g/kg and 1 g/kg LA (LA0, LA500, LA1000) were designed to feed juvenile largemouth bass on a satiation diet twice daily for eight weeks with each diet feeding to triplicate groups. The results indicated that the performance in growth was significantly enhanced by the addition of dietary LA (p < 0.05). Meanwhile, hepatic glycogen content was significantly reduced (p < 0.05), and the expression of genes relating to insulin pathway and glycolysis significantly increased with LA inclusion (p < 0.05). The relative expression of insulin receptor a (ira) in the LA500 group was the highest, while the relative expression of glycerol kinase (gk), phosphofructokinase liver type (pfkl) and phosphoenolpyruvate carboxykinase (pepck) was the highest in the LA1000 group (p < 0.05). In addition, LA supplementation significantly increased the activity of lysozyme, which reached its maximum value in the LA500 group (p < 0.05). LA supplementation also promoted the expression of genes relating to anti-inflammatory and inhibited the expression of pro-inflammatory related genes (p < 0.05). Above all, the dietary addition of LA could improve performance in growth, alleviated hepatic glycogen deposition, and improved the immunity function of largemouth bass fed on high dietary carbohydrates. This provides us with ideas to mitigate the adverse effects of high carbohydrates on largemouth bass in actual production and provides a basis for the application of LA in aquatic biology.